What makes a high-quality exporter? Evidence from Germany - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This paper uses a tailor-made newly available data set to investigate for the first time the links between the quality of input factors and the quality of exports in enterprises from manufacturing industries in Germany, one of the leading actors on the world market for goods. The paper demonstrates that in German manufacturing industries exporters of high-quality goods tend to use high-quality inputs, while the firm size is not related at all to export quality.
Keywords: F14; 330; Exports; export quality; Germany